Hubungan Minat Membaca dan Penguasaan Retorika dengan Kemampuan Menulis Teks Pidato: Penelitian Korelasi di SMP Muhammadiyah 3 Jakarta - Suwarto Suwarto (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This thesis aims to find out how big the correlation relationship Interests Reading and Writing Ability Mastery rhetoric with Text To Speech to students of SMP Muhammadiyah 3 Jakarta. The population in this study is the eighth grade students of SMP Muhammadiyah 3 Jakarta 135 the number of students. Samples were taken 50% in order to get a sample size of 68 students consisting of 2 (two) classes, VIII1 and VIII2. Collecting data using questionnaires, practical and written tests. Test requirements analysis test was used for normality, linearity and multicollinearity. The analysis technique used is the product moment correlation. This study used survey method as this method is considered appropriate to gather information or data that is used to determine the mutual relationship between the dependent variable, ie writing text to speech (Y) with independent variables, namely interest in reading (X1) and mastery of rhetoric (X2). Based on the results obtained in this study can be concluded as follows: (1) there is a positive and significant relationship between interest in reading by writing text to speech students of SMP Muhammadiyah 3 Jakarta (ry.x1 = 0.45) at level α = 0, 05 this suggests that if the interest in reading is increased then write the speech text will increase. Vice versa, if the interest in reading low then write the speech text will also decrease. The coefficient of determination (r2 = 0.2025) indicates that 20.25% of variance determined to write text to speech reading interests. (2) there is a positive and significant correlation between mastery of rhetoric by writing a speech text three students of SMP Muhammadiyah 3 Jakarta (ry.x2 = 0.46) at the level of α = 0.05. This shows that if the mastery of rhetoric increased then write the speech text will also increase. Vice versa, if the lower mastery of rhetoric it will also lower the level of writing text to speech. The coefficient of determination (r2 = 0.2116) indicates that 21.16% of variance to write text to speech is determined by the mastery of rhetoric; and (3) There is a positive and significant relationship between reading and mastery of rhetoric together with the written text to speech (ry-1.2 = 0.8 at the level of α = 0,05.hal This shows that if interest in reading and mastery of rhetoric together increased then write the speech text will also increase. the result of the determination coefficient (r2 = 0.59), which showed that 59% variance to write text to speech is determined by reading and mastery of rhetoric together.